A novel medium heavy alloy (MHA) with excellent static/dynamic properties and impact toughness. (15th March 2019) - Li, Y.; Liu, G.Q.; Hu, X.B.; Wu, L.H.; Tan, C.W.; Dravid, Vinayak P.; Liu, S.Z.
Abstract: Conventional tungsten heavy alloys (WHAs) fabricated using powder metallurgic method exhibit a much lower strength than ultrahigh strength steels (UHSSs). Here, we first time designed a novel medium heavy alloy (MHA) of 57Ni-37W-5Co-1Ta fabricated using the casting technology. Compared to WHA, this MHA not only largely reduces the difficulty in manufacturing and post working, but also enhances the toughness by ~10 times together with excellent quasi-static and dynamic properties. The superior strength-toughness is attributed to the face-centered cubic (FCC) matrix and/or the nano-sized secondary phases. While the superior dynamic performance is attributed to the widening of adiabatic shear bands (ASBs). Graphical abstract: Unlabelled Image